EFEK EKSPANSI MEDIA MASSA BARAT DAN IMPERIALISME BAHASA - Wibowo, Novin Farid Styo (Universitas Muhammadiyah Surakarta, 2011)
Change of use of the term Indonesian into English terms being common done either by formal, non- formal institutions and community. Its use not only as a companion, but replaces the old term in the Indonesian language in full. This condition is a consequence be experienced by third world countries due to globalization. Analysis the structure of macro-historical views of Western influenced into the third world countries, especially Indonesia, particularly the use and control of mass media as a means of penetration of cultural change. Analysis is also based by several studies approach that are hegemony, domination, depedence, cultural imperialism and postcolonialism.?